Blakea nareliana (Melastomataceae), a new species from the upper Huallaga in Northern Peru - Bussmann, Rainer W. (2013)
A new Peruvian species of Blakea(Melastomataceae) is described. Blakea nareliana is a small tree, endemic to the cloud forest zone in the northern Andean Huallaga area of Peru. This region is highly diverse and under-collected due to difficult access. Currently the new species is only known from one population at the type locality. However, extensive collections in the wider region have led to the discovery of many previously unknown populations of other rare Melastomataceae. It is to be hoped that future collecting efforts in the region will yield more material of Blakea nareliana.